LEGAL ASPECTS IN PROMOTING THE DYNAMICS OF UPSTREAM INDRAGIRI HULU ECONOMIC DEVELOPMENT - Yusnedi Yusnedi; Raja Marwan Indra Saputra (JURNAL MANAJEMEN DAN BISNIS, 2021)
The background of this research is a field experiment which finds that there are many emerging businesses and after observing there is a comparison of developing and undeveloped businesses. One of the things that affect it is the lack of capital and requires subsidized funds which of course will be difficult to obtain. The difficulty in finding additional funds is inseparable from the role of legal aspects in business. However, the purpose of this research is inseparable from the concept of management which shows the role of its impact on economic development in Indragiri Hulu. The research method uses qualitative methods which are described to look for issues of economic development and community difficulties in obtaining the legal standing of the business being run. This legal standing, of course, is based on licensing, the stages of which are poorly understood. The role of this legal standing can be conveyed to the general public, so that more and more businesses have businesses that have permits, so that in obtaining sources of funds for the development of the business concerned, and of course it can support the regional economy, especially the Indragiri Hulu Regency. As a result, government participation must be quantifiable, implying that the government considers the amount to which it intervenes in the economy in three ways: (1) as a regulator, (2) as a provider, and (3) as an entrepreneur. While the most essential purpose of the law is to give certainty in the conduct of economic transactions. The government's primary responsibility is to enforce the law. and the main function of law is social progress and better standards of life.